Pengaruh Kapasitas Memori RAM (Random Access Memory) Terhadap Kecepatan Memori Pada Laptop - Farah Humainah, Ratu; Firmansyah, Arjuna Fikri Tri; Ramadhani, Shafwan Iman; Didik Aribowo (Politeknik Kampar, 2023)
The memory on a laptop is very important as it is the main component of the laptop, memory which is usually used to store information for direct use on the laptop. Memory also consists of RAM (Random Access Memory), where if the RAM has a higher capacity or storage, the device operates quickly and easily. Therefore, this research will discuss memory, which aims to determine the effect of memory capacity on memory speed, which in this research uses three (3) laptops, laptop X, laptop Y and Laptop Z. Laptop X has AMD Ryzen 5 5600H processor specifications. with Radeon Graphics and 8.00 GB RAM (8.41 GB unused) and laptop Y has Intel® Core™ i3-1005G1 processor specifications and 4.00 GB RAM (3.75 GB unused), while Laptop Z has AMD A6-5200 APU processor specifications with Radeon™ HD Graphics and 2.00 GB RAM(1.47 GB unused). Testing the validity and reliability of the instrument but the description of the symbols on the model is written in sentences. Therefore, memory that has a higher RAM capacity or larger RAM has fast memory performance speed and is easy to operate, while laptops that have small RAM have low performance speed which results in low performance speed and results in slow performance.